Menyoal Kegentingan dan Pasal Impunitas Dalam Perppu Corona - Siti Nurhalimah (ADALAH, 2020)
Abstract:The weakening of business activities due to the Corona pandemic has reduced state revenues, while increasing the cost of state expenditure (Economic Instability). If it is not handled carefully and immediately, it is feared that this pandemic will cause a long-term effect and impact on the sustainability of national economic instability. The government then issued regulations regarding financial hurdles and stability of the country's financial system through the "Perppu" legal product, which was colored by positive responses and millions of criticisms, mainly due to the alleged existence of an article giving impunity to KSSK officials. The Perppu that was compiled in "abnormal" conditions certainly cannot be said to be perfect. Therefore, the DPR as the legislator as well as the representation of all the people should review the intent and substance of the Perppu.Keyords: Corona pandemic, State Finances, Impunity Abstrak:Melemahnya aktifitas dunia usaha akibat pandemi Corona telah menurunkan pendapatan negara, sekaligus meningkatkan biaya belanja negara (Instabilitas Ekonomi). Jika tidak ditangani dengan cermat dan segara, dikhwatirkan pandemi ini menimbulkan long-term effect dan berimbas pada instabilitas ekonomi nasional yang berkelanjutan. Pemerintah kemudian menerbitkan regulasi mengenai kebijakan keuangan dan stabilitas sistem keuangan negara melalui produk hukum “Perppu" yang diwarnai berbagai respond positif serta jutaan kritik, terutama karena dugaan adanya pasal yang memberi impunitas kepada pejabat KSSK. Perppu yang disusun pada kondisi “tidak normal” ini tentu tidak dikatakan sempurna. Oleh karenanya, DPR sebagai pembentuk undang-undang sekaligus representasi seluruh rakyat patut mengkaji kembali maksud serta subtansi Perpu tersebut. Kata Kunci: Pandemi Corona, Keuangan Negara, Impunitas